Demographics and Psychological Factors of Individual Investors and Investment Bias - Tharshiga, P.; Yogendrarajah, R. (Rajarata University of Sri Lanka, 2018)
Personality is a set of individual differences that are affected by the development of an individual such as values, attitudes, personal memories, social relationships, habits, and skills. Different personality theorists present their own definitions of the word based on their theoretical positions. The term "personality trait" refers to enduring personal characteristics that are revealed in a particular pattern of behaviour in a variety of situations. The researchers selected demographic factors and five personality traits of individual investors, such as openness, conscientiousness, extraversion, agreeableness, and neuroticism as the independent variables and investment biases as the dependent variables. For the study purpose, 500 questionnaires were distributed to the CSE investors but the response rate was 67%. Path analysis was used to find out the relationships among demographics, psychological factors of individual investors and investment bias. The results reveal that overconfidence bias is influenced by marital status, age and education of the individual investors. Herding bias is affected by age, education and gender of the individual investors. Deposition effect is influenced by religion of the individual investors. Further, the education level and age has significant negative relationship with herding and over confidence bias. Overconfidence bias has significant positive relationship with conscientiousness, neuroticism, openness and extrovert. Herding bias has positive significant relationship with neuroticism, openness and extrovert. Deposition effect has significant positive relationship with neuroticism, agreeableness and extrovert. The researchers recommend that the investors should be aware of psychological biases with which they can face by knowing their own personality traits and make decisions depending on their financial risk. The educated individuals should evaluate the investment's programs consciously and consult with others about their own ideas. Women and young individuals are recommended to follow experts' experiences and accept the market's information and use them in their investments.
Keywords: Demographics factors; Investment bias; Psychological factors